The Effect of Work Environment, Work Discipline and Motivation on Employee Satisfaction - Kurniawan, Rahmad; Mahdani, Rimal (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The marketing communication strategy of Toska Fashion is designed to increase customer engagement through the company website. In the current business environment, competition is intensifying, with companies facing increasing pressure to refine their communication strategies and highlight the advantages of their products. Matahari, a retailer offering both local and international clothing, has encountered challenges in online marketing. This presents an opportunity to examine the effectiveness of the marketing communication strategy, particularly in the context of websites integrated with social media platforms such as Instagram. The objective of these methods is to enhance customer engagement with Matahari Fashion products. The process of building customer engagement is comprised of several key elements, including the utilization of advertisements, the integration of shopping features on social media, the implementation of campaigns with prizes, the monitoring of after-sales interactions, and the engagement with social media features. These elements are expected to contribute to an increase in Matahari's customer engagement, which in turn should result in an uptick in the number of sales transactions.